A Phase II randomized study of galunisertib monotherapy or galunisertib plus lomustine compared with lomustine monotherapy in patients with recurrent glioblastoma. Issue 8 (21st February 2016) - Brandes, Alba A.; Carpentier, Antoine F.; Kesari, Santosh; Sepulveda-Sanchez, Juan M.; Wheeler, Helen R.; Chinot, Olivier; Cher, Lawrence; Steinbach, Joachim P.; Capper, David; Specenier, Pol; Rodon, Jordi; Cleverly, Ann; et al.
Abstract: Background: The combination of galunisertib, a transforming growth factor (TGF)-β receptor (R)1 kinase inhibitor, and lomustine was found to have antitumor activity in murine models of glioblastoma. Methods: Galunisertib (300 mg/day) was given orally 14 days on/14 days off (intermittent dosing). Lomustine was given as approved. Patients were randomized in a 2:1:1 ratio to galunisertib + lomustine, galunisertib monotherapy, or placebo + lomustine. The primary objective was overall survival (OS); secondary objectives were safety, pharmacokinetics (PKs), and antitumor activity. Results: One hundred fifty-eight patients were randomized: galunisertib + lomustine (N = 79), galunisertib (N = 39), and placebo + lomustine (N = 40). Baseline characteristics were: male (64.6%), white (75.3%), median age 58 years, ECOG performance status (PS) 1 (63.3%), and primary glioblastoma (93.7%). The PKs of galunisertib were not altered with lomustine, and galunisertib had a median half-life of ∼8 hours. Median OS in months (95% credible interval [CrI]) for galunisertib + lomustine was 6.7 (range: 5.3–8.5), 8.0 (range: 5.7–11.7) for galunisertib alone, and 7.5 (range: 5.6–10.3) for placebo + lomustine. There was no difference in OS for patients treated with galunisertib + lomustine compared with placebo + lomustine [P (HR < 1) = 26%]. Median progression-free survival of ∼2 months was observed in all 3 arms. Among 8 patients with IDH1 mutation, 7 patients were treated with galunisertib (monotherapy or with lomustine); OS ranged from 4 to 17 months. Patients treated with galunisertib alone had fewer drug-related grade 3/4 adverse events ( n = 34) compared with lomustine-treated patients (10% vs 26%). Baseline PS, post-discontinuation of bevacizumab, tumor size, and baseline levels of MDC/CCL22 were correlated with OS. Conclusions: Galunisertib + lomustine failed to demonstrate improved OS relative to placebo + lomustine. Efficacy outcomes were similar in all 3 arms. Clinical Trial Registration: NCT01582269, ClinicalTrials.gov.